Computational analysis of new PCPDTBT derivatives in monomer state: Substitutions effect of Si and Ge on the optoelectronic properties and performance of photovoltaic device - Hssaın, Ala; Mohammad, Suhaib; Elyas, Danar; Bulut, Niyazi (Niyazi BULUT, 2025)
The study used Density functional theory (DFT) to analyze the structural, electrical and optical properties of PCPDTBT derivatives as an organic molecule in a monomer state that is substituted with Silicon and Germanium as well as 2-ethyl-hexyl replaced by a 2-methyl group for use in OPVs. The substitutions decreased the band gap energy (Eg), with Si-PCPDTBT and Ge-PCPDTBT having the Eg of 1.52 eV and 1.51 eV, respectively. FMOs analysis, molecular electrical properties, MEP, VOC, NCI, DOS, ELF, and refractive index of the molecules are computed using PBEPBE/6-311G+ (d, p) methods. Next, spectroscopic analyses are carried out utilizing UV-vis spectroscopies in gas phase, chloroform, and chlorobenzene solvents. The Eg and VOC are improved compared to the PCPDTBT. From the dipole moment, the Ge-PCPDTBT has stronger intermolecular interaction which is comparable to the Eg, and its refractive index in chloroform solvent is found to be higher than that of the Si-PCPDTBT.
Keywords: Atomic and Molecular Physics; Atom ve Molekül Fiziği